Coupled T-H-M processes' effect on specific energy in continuous wave fiber laser rock perforation - Erfan, M.; Shahriar, K.; Sharifzadeh, Mostafa; Ahmadi, M.; Mousavi, M. (2018)
Laser perforation of oil and gas wells is a new method for well completion as an alternative to blasting methods. Under real perforation in oil and gas wells, three main factors have influence on the laser perforation such as specific energy (i.e., energy required to remove the unit weight of rock). These three factors are temperature, the hydraulic pressure of fluid flow, and confining pressure. This paper investigates the role and significance of the coupled T-H-M (thermo-hydraulic-mechanical) processes on specific energy (SE) and rate of penetration (RoP). For physical modeling of T-H-M processes, a new cell and setup is designed and developed. In this setup, a circular part of the front side of the cylindrical sample is open in order to interact with the laser beam while the temperature, hydraulic pressure, and confining pressure are applied to the sample. The rock tested under four temperature steps from 25 to 120 °C (temperature range of major oil reservoir in fractured rocks), the hydraulic pressure was chosen in five steps from 0 to 35 MPa (fluid pressure range of more than 70% of Iranian oil reservoir rocks), and confining pressure was selected from 0 to 40 MPa (ranges of overburden pressures). Test results show rises in specific energy with incremental increases in rock temperature, hydraulic pressure, and confining pressure, while the rate of penetration decreases.